Bacteria-derived hydrogen sulfide promotes IL-8 production from epithelial cells - Chen, Weilin; Kajiya, Mikihito; Giro, Gabriela [UNESP]; Ouhara, Kazuhisa; Mackler, Harrison E.; Mawardi, Hani; Boisvert, Heike; Duncan, Margaret J.; Sato, Kimihiro; Kawai, Toshihisa (Academic Press Inc. Elsevier B.V., 2010)
Hydrogen Sulfide (H(2)S) a volatile Sulfur compound, is implicated as a cause of inflammation. especially when it is produced by bacteria colonizing gastrointestinal organs However, It IS Unclear if H(2)S produced by periodontal pathogens affects the inflammatory responses mediated by oral/gingival epithelial cells Therefore. the aims of this Study were (1) to compare the in vitro production of H(2)S among. 14 strains of Oral bacteria and (2) to evaluate the effects of H(2)S on inflammatory response induced in host oral/gingival epithelial cells Porphyromonas gingivalis (Pg) produced the most H(2)S in Culture, Which, in turn resulted in the promotion of proinflammatory cytokine IL-8 from both gingival and Oral epithelial cells The up-regulation of IL-8 expression was reproduced by the exogenously applied H(2)S Furthermore. the Mutant Strains of Pg that do not produce major Soluble Virulent factors. ie gingival, still showed the Production of H(2)S. as well as the promotion of epithelial IL-8 production. which was abrogated by H(2)S scavenging reagents These results demonstrated that Pg produces a concentration of H(2)S capable of Up-regulating-IL-8 expression induced in gingival and oral epithelial cells, revealing a possible mechanism that may promote the inflammation in periodontal disease (C) 2009 Elsevier B.V. All rights reserved
Keywords: Hydrogen sulfide; Epithelial cells; IL-8; Bacteria; Porphyromonas gingivalis; Gingipain; Pathogenesis; Hydrogen; Innate immune response; Periodontal disease